Attempt to Unificate the Debts of the Ottoman Empire (1903) - KarataŞ, Yakup (Dunakavics, 2024)
It is known that throughout Ottoman history, the state developed and used internal borrowing methods when it needed cash. Various efforts to raise funds through methods such as transfers from the internal treasury, "mukataa", "malikane", "esham", forcing statesmen to donate, borrowing from money changers and bankers, and confiscation are evident. No loans were taken from a foreign country until the second half of the 19th century. In 1854, during the Crimean War, a loan was taken from England for the first time. Over time, the amount of foreign capital entering the country increased and the state became unable to pay them and declared bankruptcy in 1875. With the Muharrem Decree in 1881, Public Debt Administration was established and a payment system for debts was established. However, the financial independence of the state has also been disrupted. Consolidation of debts, an extraordinary practice that draws attention in the payment of debts, constitutes the main theme of this presentation. Documents on the subject in both the Ottoman Archives and the British Archives regarding the implementation methods of the Ottoman administration, which wanted to consolidate and prioritize the accumulated debts, will serve as the source of this study. These documents will be examined comparatively and their effects on the field of application and the management content applied during the payment of debts will be explained. This subject, which is multidimensional and has predominant technical aspects, has been discussed in general terms in its historical integrity and is aimed to be a source for future studies on this subject.